Towards Trustworthy Safety Assessment by Providing Expert and Tool-Based XMECA Techniques - Babeshko, Ievgen; Illiashenko, Oleg; Kharchenko, Vyacheslav; Leontiev, Kostiantyn (Mathematics (Basel), 2022)
Safety assessment of modern critical instrumentation and control systems is a complicated process considerably dependent on expert techniques, single/multiple faults consideration scope, other assumptions, invoked limitations, and support tools used during the assessment process. Ignoring these assumptions, as well as the significance of expert and tool influence, could lead to such effects as functional safety underestimation or overestimation in such a manner that functional safety assessment correctness and accuracy are affected. This paper introduces XMECA (x modes, effects, and criticality analysis, where x could be from different known techniques and domains—failures in functional safety, vulnerabilities and intrusions regarding cybersecurity, etc.) as a key technique of safety assessment. To verify the results obtained as XMECA deliverables, expert and uncertainty modes, effects, and criticality analysis (EUMECA) is performed, in particular focusing on decisions and judgments made by experts. Scenarios for processing verbal and quantitative information of XMECA tables from experts are offered. A case study of a possible functional safety assessment approach that considers the above-mentioned techniques and a supporting tool is provided. To assess the trustworthiness of safety analysis and estimation using XMECA, a set of the metrics is suggested. Features of adapting the suggested method for security assessment considering intrusions, vulnerabilities, and effects analysis (IMECA technique) are discussed.